Stress–strain model for FRP confined heat-damaged concrete columns. (April 2023) - Shayanfar, Javad; Barros, Joaquim A.O.; Rezazadeh, Mohammadali
Abstract: This paper is dedicated to the development of a new analysis-oriented model to simulate the axial and dilation behavior of FRP confined heat-damaged concrete columns under axial compressive loading. The model's calibration has considered the experimental results from concrete circular/square cross-section specimens submitted to a certain level of heat-induced damage, which after attained the environmental temperature, were fully confined with FRP jacket and tested. New equations were developed to determine the mechanical characteristics of unconfined heat-damaged concrete by performing regression analysis on a large database of experimental tests. Based on a parametric study on dilation behavior of FRP confined heat-damaged columns, a new dilation model was developed to predict concrete lateral strain at a given axial strain, dependent on the thermal damage level. By using this dilation model, a new methodology was introduced for predicting the axial stress-strain response of FRP confined heat-damaged columns in compliance with the active confinement approach . The adequate predictive performance of the model is demonstrated by estimating experimental axial stress-strain results. Highlights: New equations for the calculation of the mechanical characteristics of unconfined heat-damaged concrete are proposed. A new methodology to reflect the influence of the thermal damage level on FRP confinement-induced improvement is introduced. Proposed analysis-oriented model revealed an adequate predictive performance.